Evaluate 1 7 6 × 1 7 2 × 1 6 8 ( 1 7 7 2 − 1 7 5 2 ) ( 1 7 3 2 − 1 7 1 2 ) ( 1 6 9 2 − 1 6 7 2 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We know a 2 − b 2 = ( a + b ) ( a − b ) Therefore, 1 7 6 × 1 7 2 × 1 6 8 ( 1 7 7 2 − 1 7 5 2 ) ( 1 7 3 2 − 1 7 1 2 ) ( 1 6 9 2 − 1 6 7 2 ) . 1 7 6 × 1 7 2 × 1 6 8 ( 1 7 7 + 1 7 5 ) ( 1 7 7 − 1 7 5 ) ( 1 7 3 + 1 7 1 ) ( 1 7 3 − 1 7 1 ) ( 1 6 9 + 1 6 7 ) ( 1 6 9 − 1 6 7 ) . = 1 7 6 × 1 7 2 × 1 6 8 ( 2 × 1 7 6 ) ( 2 ) ( 2 × 1 7 2 ) ( 2 ) ( 2 × 1 6 8 ) ( 2 ) . = 2 6 = 6 4
Don't worry by looking at question's title. It's not complicated.
First, separate all the terms of the numerator and solve each and finally combine them all.
First term
\( 177^{2} \) - \( 175^{2} \)
The average of the two terms 177 and 175 is 176. It can also be expressed like this.
{\( (176 + 1)^{2} \) - \( (176 - 1)^{2} \)}
By using the formula of \( a^{2} \) - \( b^{2} \)
Please note that here our a is (176 + 1) and our b is (176 - 1)
So,
( 176 + 1 + ( 176 -1)) (176 + 1 -(176 - 1))
= ( 176 + 1 + 176 - 1) (176 + 1 - 176 + 1)
=(176 + 176) ( 1+ 1)
=( 2 * 176) * 2
= 176 * 2 * 2
Second term
\( 173^{2} \) - \( 171^{2} \)
The average of the two terms 173 and 171 is 172. It can also be expressed like this.
{\( (172 + 1)^{2} \) - \( (172 - 1)^{2} \)}
By using the formula of \( a^{2} \) - \( b^{2} \)
Please note that here our a is (172 + 1) and our b is (172 - 1)
So,
( 172 + 1 + ( 172 -1)) (172 + 1 -(172 - 1))
= ( 172 + 1 + 172 - 1) (172 + 1 - 172 + 1)
=(172 + 172) ( 1+ 1)
=( 2 * 172) * 2
= 172 * 2 * 2
* Third term *
\( 169^{2} \) - \( 167^{2} \)
The average of the two terms 169 and 167 is 168. It can also be expressed like this.
{\( (168 + 1)^{2} \) - \( (168 - 1)^{2} \)}
By using the formula of \( a^{2} \) - \( b^{2} \)
Please note that here our a is (168 + 1) and our b is (168 - 1)
So,
( 168 + 1 + ( 168 -1)) (168 + 1 -(168 - 1))
= ( 168 + 1 + 168 - 1) (168 + 1 - 168 + 1)
=(168 + 168) ( 1+ 1)
=( 2 * 168) * 2
= 168 * 2 * 2
Now, combining all the terms.
(\( 177^{2} \) - \( 175^{2} \))(\( 173^{2} \) - \( 171^{2} \))(\( 169^{2} \) - \( 167^{2} \)) divided by 176 * 172 * 168
= 2 * 2 * 176 * 2 * 2 * 172 * 2 * 2* 168 divided by 176 * 172 * 168
= 2 * 2 * 2 * 2 * 2 * 2
= 64
Hence, our final answer is 64.
1 7 6 × 1 7 2 × 1 6 8 ( 1 7 7 2 − 1 7 5 2 ) ( 1 7 3 2 − 1 7 1 2 ) ( 1 6 9 2 − 1 6 7 2 ) = a = 1 7 6 . . . a = 1 7 2 . . . a = 1 6 8 a ( a + 1 ) 2 − ( a − 1 ) 2 = 4 1 7 6 × 1 7 2 × 1 6 8 ( 1 7 7 2 − 1 7 5 2 ) ( 1 7 3 2 − 1 7 1 2 ) ( 1 6 9 2 − 1 6 7 2 ) = 4 × 4 × 4 = 6 4
If we factor the expression into three fractions in which the numerator is the difference of perfect squares and the denominator is the mean of the bases of those squares:
(a^2-b^2)/((a+b)/2)
then ((a+b)(a-b))/((a+b)/2)
simplifies to 2*(a-b)
and since in each case a - b = 2
each of the three fraction simplifies to 2 * 2
we now have (2 * 2)(2 * 2)(2 * 2)
or 2^6 = 64
See that all the multiples of the numerator are of the form ( n + 2 ) 2 − n 2 Which simplifies to 4 n + 4 So setting n = 1 7 5 , 1 7 1 a n d 1 6 7 ,we get 7 0 4 , 6 8 8 a n d 6 7 2 ,So: 1 7 6 × 1 7 2 × 1 6 8 ( 1 7 7 2 − 1 7 5 2 ) ( 1 7 3 2 − 1 7 1 2 ) ( 1 6 9 2 − 1 6 7 2 ) = 1 7 6 × 1 7 2 × 1 6 8 7 0 4 × 6 8 8 × 6 7 2 = 4 4 × 4 3 × 4 2 1 7 6 × 1 7 2 × 1 6 8 = 4 × 4 × 4 = 4 3 = 6 4
Looking to the denominators we find that are like (a2-b2)(c2-d2)(m2-n2) we can put them as (a+b)(a-b)(c+d)(c-d)(m+n)(m-n) ,substituting given values in numerators and denominators,we get 2X2X2X2X2X2 =64 Ans K.K.GARG,India
don't blindly multiply--use (a^2-b^2)=a+b*a-b
i done by the rule
Problem Loading...
Note Loading...
Set Loading...
We first see that 1 7 7 2 − 1 7 5 2 = 2 ( 1 7 7 + 1 7 5 ) . 2 ( 1 7 7 + 1 7 5 ) = 2 ( 2 ⋅ 1 7 6 ) . Therefore, if we just look at 1 7 6 1 7 7 2 − 1 7 5 2 , we have a quotient of 4 . By doing the same to 1 7 2 1 7 3 2 − 1 7 1 2 and 1 6 8 1 6 9 2 − 1 6 7 2 , we have a product of 4 ⋅ 4 ⋅ 4 = 6 4 as our answer.